Analysis of Outpatient Satisfaction and the Quality of Health Services - Sumayyah Jamal H. M. Arifin; Muntasir Muntasir; Erny Erawati Pua Upa (Universitas Nusa Cendana, 2020)
Quality is an important factor in health services. Bakunase Health Center is one of the primary accredited health centers in Kupang City. Based on data from the Health Department, there has been a decrease in the number of visits over the last three years. This happens due to external factors and internal factors. The external factor is the increasing degree of public health, while the internal factor is the decrease in the patients’ commitment to treatment. The purpose of this study is to describe the level of outpatient satisfaction with the quality of health services at Bakunase Health Center of Kupang City in 2020. This was a descriptive survey with a quantitative approach. The population in this study was all patients who visited and used outpatient services at Bakunase Health Center in Kupang City from January to October 2019. Accidental sampling was used in selecting the samples from each outpatient sub-group in 7 polyclinics at Bakunase Health Center using inclusion and exclusion criteria. The results indicated that the level of conformity between expectations and reality of the services are as follows: 98.78% tangible, 98.66% reliable, 98.33% responsive, 98.79% assurance 98.74% empathy. Based on the Cartesian Importance Performance Analysis (IPA) diagram, quadrant A was filled by one attribute from the responsiveness dimension, quadrant B was filled by most attributes from the reliability dimension, quadrant C was filled by most attributes from the empathy dimension and quadrant D was filled by one attribute from the responsiveness dimension.